Ascensão e queda da Unasul: ideologia, política externa e integração regional na América do Sul (2008-2022) - Corrêa, Tammy Eduarda (2024)
The expansion of the International Relations discipline allows new contexts to be added to academic observation, encompassing the study of specific regions of the global south and regional phenomena, as is the case of South America. The research uses a historical-comparative perspective and seeks to identify what explains the rise and decline of Unasur between 2008 and 2022? In and underlying way, we sought to understand the institutionalization degree of cooperation and integrative features of a decade characterized by the ideological transition from progressivism to conservatism. The study examines the period from 2008 to 2022 and depicts it through the political and ideological particularities in South America, especially regarding political consonances, covered by the phenomena of the pink tide and the conservative wave. The main hypothesis is that ideological convergence and divergence influence the South American context and its trends and sorts of regional integration. Two crucial nations for the analysis are Argentina and Brazil which, through government transitions and ideologies in power, influence changes in the type of interaction and regional integration through their foreign policies. As a result, Unasur underwent a process of emptying under the criticism of political-ideological bias. Specifically, we will seek to: a) analyze recent regional political trends; b) identify similarities and particularities of governments that shifted towards right-wing parties; c) verify at the South American level (Argentina, Brazil, Chile, Ecuador, Paraguay and Peru) the integrative blocs and projects that were impacted during the period; d) explore the axis of convergence/alignment and divergence/distancing between Argentina and Brazil; e) understand the emptying of Unasur and its political-ideological conditioning. The importance of the research rests on registering transitional characteristics towards conservatism and the implementation of adjacent right-wing governments in the region, underpinning new values of regional and global insertion.The importance of the research lies in recording the ideological impact on foreign policy framing, which influences directly on regional integration between South American countries.